Analysis of Green Product, Green Advertising, Green Perceived Value, Green Trust, and Green Purchase Intention of Aqua Product in Special Region of Yogyakarta - Nurhalisa, Suci; Wahyuningsih, Tri; Liestyana, Yuli; Utami, Yekti; Tugiyo, Tugiyo (Journal of International Conference Proceedings, 2023)
Consumer's concern for environmental sustainability raises consumption behavior for environmentally friendly products . This study investigates the impact of green products, green advertising, and green perceived value on green purchase intention, with green trust serving as a moderating variable. The population of this research is all consumers of AQUA product in Yogyakarta. The sample of 190 respondents has been chosen with the The technique of purposive sampling. The Partial Least Squares (PLS) method is used in this study to test hypotheses. based Structural Equation Model (SEM) approach.Â  The data collection method uses a Likert scale. Based on the research results, green products, green advertising, and green perceived value significantly influence green trust. There is a Green Trust, substantial Effect on green purchase intention. Green trust acts as a bridge between green products and green purchase intent. Green trust serves as a link between green advertising and green buying intent. Green trust acts as a bridge between green perceived value and green buying intent.